2021
DOI: 10.2306/scienceasia1513-1874.2021.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sandalwood oil on inhibition of reactive oxygen species generation and lipopolysaccharideinduced inflammation through down-regulation of the nuclear factor-κB signaling pathways

Abstract: We investigated the antioxidative and anti-inflammatory effects of sandalwood oil and attempted to elucidate its underlying mechanism of action. The antioxidant activities of sandalwood oil were assessed using various methods: 1.1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2 -azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS + ) radical scavenging assays, as well as DNA protection ability and reactive oxygen species (ROS) generation. The cell viability of sandalwood oil in RAW 264.7 cells (murine macrophage)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…LPS is a major component of the membrane of Gram-negative bacteria, and it is also an endotoxin that causes immune response. In the human body or in cell line in vitro study, LPS binds to the lipopolysaccharide receptor complex (CD14/TLR4/MD-2) on the cell membrane and promotes the secretion of a variety of cytokines in inflammatory cells [18]. Inflammation and cell viability are closely related to many coronary artery diseases, such as acute myocardial infarction, ischemic heart disease, and microvascular reperfusion injury [19].…”
Section: Discussionmentioning
confidence: 99%
“…LPS is a major component of the membrane of Gram-negative bacteria, and it is also an endotoxin that causes immune response. In the human body or in cell line in vitro study, LPS binds to the lipopolysaccharide receptor complex (CD14/TLR4/MD-2) on the cell membrane and promotes the secretion of a variety of cytokines in inflammatory cells [18]. Inflammation and cell viability are closely related to many coronary artery diseases, such as acute myocardial infarction, ischemic heart disease, and microvascular reperfusion injury [19].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we supposed that DUB3 may regulate EZH2 to affect cancer progression. Nuclear factor-kappaB (NF-κB) is a transcription factor that induces signal transduction between nucleus and cytoplasm in many cell types [13]. Hypoxia-inducible factor-1α (HIF-1α) is a subunit of HIF-1 transcriptional factor [14].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the main treatment of these diseases is limited to dental/surgical repair, antibiotics, and nonsurgical mechanical debridement [3]. Lipopolysaccharide (LPS) is a main component of the outer membrane of Gram-negative bacteria, which can cause inflammation [4,5]. In vivo assays showed that LPS promotes the osteoclastic activity by upregulating the expression of Receptor Activator for Nuclear Factor-κB Ligand (RANKL) [6].…”
Section: Introductionmentioning
confidence: 99%